Isthmocele: emerging emergency - Todani, Ashok Kumar; Todani, Kiranlata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
An isthmocele, a caesarean scar defect or uterine niche, is any indentation representing myometrial discontinuity or a triangular anechoic defect in the anterior uterine wall, with the base communicating to the uterine cavity, at the site of a previous cesarean section scar. With rise of caesarean sections, incidence of isthmocele and scar ectopics is on rise, being 19 to 88% in caesarean delivery patients. As there are no definitive criteria for diagnosing an isthmocele, several imaging methods can be used to assess the integrity of the uterine wall and thus diagnose an isthmocele. However, transvaginal ultrasound and saline infusion sonohysterography emerge as specific, sensitive and cost-effective methods to diagnose isthmocele. When cervix is encroached as well by ectopic placentation, situation becomes much more alarming and grave. Timely diagnosis and active management of the entity is a must to save life of patient. Area of isthamocele bearing ectopic gestation sac has to be excised whatever be the method, by endoscopy or conventional open method. Previous gestation scar dehiscence or rupture of uterus repair leads to more weakness and impaired integrity of uterine wall. If patient refuses to undergo simultaneous sterilization, recurrence of isthmocele formation and ultimate scar ectopic will be even higher. Here we presented a case of ectopic gestation in isthmocele complicated by its extension to cervix with an associated posterior wall cervical fibroid at same level.